(3aj Xd JcfhdhLjG GdeYdheGJs - (3ceGd GdOjf eUWai(B, (3GdOgQGhjs ((3GdGScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2007)
(3GdeaGgje GdGSGSjI dfXe GdeYdheGJ h JTZjd GdeYdheGJ aj fXGe GdeYdheGJ GdeMGSHj hOhQI GdYedjGJ (B.s
Keywords: (3GdeMGSHIs; (3GdeYdheGJs; (3JcfhdhLjG GdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s